2017
DOI: 10.13057/nusbiosci/n090107
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of top soil and fertilizer mixture to improve the ex-coal mining land

Abstract: Abstract. Sopialena, Rosfiansyah, Sila S. 2017. The benefit of top soil and fertilizer mixture to improve the ex-coal mining land. Nusantara Bioscience 9: 36-43. The mining activities have led severe impacts on some environmental issues including a decrease in soil fertility, which affects the ability of soil to supply soil nutrients to growing plants, a destruction in soil structure, and the loss of microorganisms, which are important for reforming process to treat organic materials. In this regards, reclamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…Pemberian topsoil Inceptisol dan kompos pada tailing merupakan upaya yang dilakukan untuk memperbaiki sifat dan kondisi tailing sehingga dapat sesuai untuk pertumbuhan tanaman. Penelitian sebelumnya yang dilakukan oleh Sopialena et al (2017) menyatakan bahwa penambahan campuran topsoil dan bahan organik pada lahan bekas tambang dapat meningkatkan pertumbuhan tanaman sengon, keragaman mikroba tanah dan kesuburan tanah, yaitu meningkatkan kandungan C, N, P2O5, dan pH tanah mendekati netral.…”
Section: Jumlah Cabangunclassified
“…Pemberian topsoil Inceptisol dan kompos pada tailing merupakan upaya yang dilakukan untuk memperbaiki sifat dan kondisi tailing sehingga dapat sesuai untuk pertumbuhan tanaman. Penelitian sebelumnya yang dilakukan oleh Sopialena et al (2017) menyatakan bahwa penambahan campuran topsoil dan bahan organik pada lahan bekas tambang dapat meningkatkan pertumbuhan tanaman sengon, keragaman mikroba tanah dan kesuburan tanah, yaitu meningkatkan kandungan C, N, P2O5, dan pH tanah mendekati netral.…”
Section: Jumlah Cabangunclassified
“…The use of organic material can improve soil fertility of ex-coal mining land (Amelia and Suprayogo, 2018). Sopialena et al (2017) reported that mixing topsoil and fertilizer on ex-coal mine land increased microbial diversity, soil fertility, and plant growth. Hermawan (2011) reported that all soil physical and chemical variables have risen to levels suitable for food crops after being reclaimed for 12 years.…”
Section: Regencymentioning
confidence: 99%
“…Topsoil accumulates biomass and large amounts of soil organic matter. Therefore, this type of substrate can act as a catalyst for the natural regeneration process (Merino‐Martín et al, 2017; Sopialena, Rosfiansyah, & Sila, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…evaluated the efficiency of using topsoil deposition with the use of leguminous and grassy species as green manure. The authors concluded that the use of legumes and grasses in soil reconstituted with topsoil can be a viable technique to recover stripped and reconstituted soils, especially by increasing the organic carbon of the soil Sopialena et al (2017). also found satisfactory results regarding soil fertility and plant growth when combining topsoil application with fertilizer for improving soil conditions when restoring land damaged by coal mining.…”
mentioning
confidence: 97%
See 1 more Smart Citation